Language and literature - Morshed, Abul Kalam Manzur; Cakama, Sugata; Asiatic Society of Bangladesh; Cultural Survey of Bangladesh Project; Cultural Survey of Bangladesh Project (Dhaka : Asiatic Society of Bangladesh, 2007)
Contributed articles published under the Cultural Survey of Bangladesh Project; covers the period, 3rd century B.C. to 20th century; includes very briefly non-Bengali literature also.
Includes bibliographical references.
00026333
In English; includes passages in Bengali.
Keywords: Bengali language -- Dialects -- Bangladesh -- History; Bengali literature -- Bangladesh -- History and criticism